Manipulation of magnetic and magneto‐transport properties of amorphous glass‐coated microwires through various annealing processes. Issue 5 (10th April 2014) - Talaat, A.; Ipatov, M.; Zhukova, V.; Blanco, J. M.; Zhukov, A.
Abstract: We studied the influence of two different kind of annealing, conventional annealing and current annealing, on the magnetic and magneto‐transport properties of amorphous Co‐Fe rich glass‐coated microwires with the nominal composition Co69.2 Fe4.1 B11.8 Si13.8 C1.1 fabricated by Taylor‐Ulitvosky technique. At a certain annealing conditions we have been able to obtain high domain wall velocity with perfectly rectangular hysteresis loop, high giant magneto‐impedance response (GMI) and almost linear with low hysteretic off‐diagonal GMI response simultaneously in the same sample. Such results could be essential from application's point of view. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)